Supporting Community-Oriented Educational Change - Mabry, Linda; Ettinger, Laura (Education Policy Analysis Archives, 1999)
A study of a federally funded program to develop and implement community-oriented social studies curricula and curriculum-based assessments grounds cautions for educational change initiatives. In this case, despite the project director's stated intent to support teachers' desire for instruction regarding local culture and history, top-down support for classroom-level change evidenced insensitivity. Production and implementation of the planned curricula and assessments was obstructed by teacher's lack of cultural identification with the targeted community groups, workload, competing instructional priorities, inadequate communication, and organizational politics. Professional development was sometimes beneficial but more often ineffective—either perfunctory, unnecessary, or disregarded. The findings offer insight regarding educational change and a systemic analysis.